Does Oil Price Fluctuation Affect Stock Market Returns in Nigeria? - Anyalechi, Kenneth Chikezie; Ezeaku, Hillary Chijindu; Onwumere, Josaphat. U. J.; Okereke, E. J. (International Journal of Energy Economics and Policy, 2018)
This paper examined the responsiveness of the stock market returns to fluctuation in oil price in Nigeria using monthly dataset from January 1994 to December 2016. The autoregressive distributed lag estimation technique was applied to analyze the long-run model as well as the short-run dynamics whereas test for cointegarating relationships was conducted using the Bound testing method. The findings revealed that changes in oil price have had positive but insignificant impact on stock market returns both in the long-run and the short-run. Impact of inflation was positive and insignificant in the long-run but positively significant in the short-run. Real interest rate and log of exchange rate exerted negative influence on the stock market returns, where the short-run effect of real interest rate was significant, the long-run impact was found to be insignificant. The error term indicates that deviation from long-run equilibrium is corrected at the speed of 8.2% on annual basis. The Bound test result showed that no long-run relationships exist between the oil price and stock market returns during the period under study. Keywords: Stock Market Returns, Oil Price, Autoregressive Distributed Lag, Bound Testing JEL Classifications: C32, Q43, E44 DOI: https://doi.org/10.32479/ijeep.7145